The public understanding of political integrity the case for probity perceptions - Rose, Jonathan; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Through detailed analyses of major and newly available datasets, this study examines the utility of a public probity-focused approach to understanding citizen disaffection with politicians. It shows that perceptions of public probity are coherent, substantively meaningful, responsive, and, most importantly, that they do matter.
Keywords: Science; Science; Science, general